PSI-18 Effect of Heat Processing Methods on Carbohydrate Subfractions and Degradation in Relation to Carbohydrate Molecular Spectral Profile of Barley Grain Using Advanced Molecular Spectroscopy in Ruminants. (21st September 2022) - Feng, X; Prates, L; Yu, P
Abstract: To our knowledge, there are few studies on the association between carbohydrate molecular structure spectral profiles of barley grain and ruminant-relevant nutritional characteristics. This study aimed to study associate processing-induced changes in carbohydrate molecular structure with changes in ruminant-relevant carbohydrate nutritional profiles. The heat processing methods included: dry roasting, autoclaving, and microwave irradiation. The ruminant-relevant carbohydrate nutritional profiles were determined which included carbohydrate chemical profiles, carbohydrate subfractions, ruminant-relevant carbohydrate digestion. The molecular structure spectral profiles were determined using vibrational molecular spectroscopy (ATR-FT/IR). The results showed that heat related processing significantly induced carbohydrate molecular spectral profiles. The heat related processing also significantly changed ruminant-relevant nutritional characteristics. There was an association between processing induced carbohydrate molecular structure changes and ruminant-relevant carbohydrate nutritional profiles. The advanced vibrational molecular spectroscopic technique (ATR-FTIR) shows the great potential as a fast analytical tool to predict ruminant-relevant carbohydrate nutritional characteristics.